New Approach to Economic Challenges - Kim, Jim Yong (World Bank, Washington, DC, 2018)
Jim Yong Kim, President of the World Bank, spoke about economic challenges requiring a new approach. Growth forecasts are modest and risks are increasing. The reform agenda includes fiscal and monetary policies to support demand, more investment in infrastructure, further integration in the world economy, structural reforms in labor markets, the financial sector, and the business climate to better allocate resource, and investment in innovation systems to accelerate technical change. One key drivers of discontent is rising inequality. The productivity slowdown and rising inequality are related. The challenge is to create wealth with reasonably equal distribution to sustain the momentum for reform. This will require active labor market policies and retraining. We will need infrastructure that connects people. We need to invest more in people. Concessional finance can provide the leverage for these reforms. We need to commit to creating a world in which truly there is equality of opportunity.